ANALISIS KESESUAIAN BUTIR SOAL KOGNITIF BUATAN GURU DENGAN INDIKATOR PENCAPAIAN KOMPETENSI DALAM MATERI BIOLOGI KELAS XI IPA DI SMA NEGERI 1 GORONTALO - Latjompoh, Masra; Hamunta, Ayun; Ibrahim, Mustamin; Solang, Margaretha; M. Hasan, Ani; Dama, Lilan (Universitas Cokroaminoto Palopo, 2024)
This research aims to analyze the suitability of teacher-made cognitive questions with indicators of competency achievement in Biology class XI Science material at SMA Negeri 1 Gorontalo. The method used is descriptive qualitative and quantitative. The subjects of this research were biology exam questions and student answers, which were analyzed based on validity, reliability, level of difficulty and distinguishing power. The research results showed that the suitability of the cognitive items with the indicators in the Learning Implementation Plan (RPP) obtained a percentage of 100%. The validity test of cognitive items in class XI IPA 1 was 0.2503 and in class The reliability test showed results of 0.4449 in class XI Science 1 and 0.3953 in class XI Science 7, which is also classified as less reliable. The test item difficulty level showed results of 0.5056 in class XI IPA 1 and 0.5267 in class XI IPA 7, which is included in the medium category. Meanwhile, the differentiating power test produced 0.1621 in class XI IPA 1 and 0.1392 in class XI IPA 7, both of which were in the weak differentiating power category.